“I CONTAIN MULTITUDES”: ABJECTION AND AFFECT IN NAMITA GOKHALE’S THE BLIND MATRIARCH (2021) - Sharma, Deeksha; Nath, Keshav (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This paper examines the interconnected themes of abjection and affects in Namita Gokhale’s novel The Blind Matriarch. The themes of abject and affect have procured substantial importance in interpreting the negotiation of marginalized bodies within patriarchal and postcolonial settings. However, Namita Gokhale’s novel The Blind Matriarch is well researched, but there has been limited attention to the combined study of all three theories. The paper examines the abject in Matangi Ma’s embodiment. It analyzes affect as emotional structuring. Further, it explores semiotic and symbolic spatial dynamics. The paper uses textual analysis and Braun and Clarke’s thematic analysis for identifying themes within the text. Using this methodology, the primary text, The Blind Matriarch, is examined through a theoretical framework that includes theories of the Abject and Affect and an analysis of semiotic and symbolic aspects. The key finding of the paper reveals that the aspect of Matangi Ma’s blindness is both marginalizing and empowering, where Matangi Ma is seen as a site of cultural contradiction. She also undermines various common conceptions of power, visibility, and gendered subjectivity. The paper concludes by showing how Matangi Ma reconfigures socio-cultural marginality through theoretical frameworks. These findings contribute to feminist literary studies by stressing the role of affect and abjection in interpreting marginalized experiences.